Validating metacognitive awareness inventory (MAI) in chemistry learning for senior high school: A rasch model analysis - Jono Irawan; Samsul Hadi; Zulandri Zulandri; Jamaluddin Jamaluddin; Abdul Syukur; Saprizal Hadisaputra (Jurnal Pijar Mipa, 2021)
This study aims to validate metacognitive instruments, which include eight indicators of declarative knowledge, procedural knowledge, conditional knowledge, planning, information management, monitoring, debugging, and evaluation. The validation method uses Rasch modeling (Item Response Theory), namely Map analysis Wright (Person-item Map), Measure DIFF, Validity (Fit Statistics for The Draft Questionnaire), Reliability Cronbach Alpha (Summary statistics). Results map analysis wright shows the distribution of items and the power of discrimination are categorized as good with the logit value around 1.0. The curve Measure DIFF and the probability value indicate that the thing does not have an element of distinguishing gender characteristics if the probability value is above 0.05. The assessment instrument's validation showed an infit-outfit of 0.5 MNSQ 1.5, an infit-outfit value of 0.5 ZSTD 1.5, and a value of 0.4 PTMEA 0.85. Furthermore, the reliability of the instrument category is excellent, with a Cronbach alpha of 0.94. In conclusion, the MAI instrument in chemistry learning was feasible to measure the metacognitive abilities of high school students.